Аналітична компетентність - ключовий складник професійної компетентності майбутніх фахівців з економічної кібернетики - Половенко, Людмила Петрівна (НТУ "ХПІ", 2012)
A concept "analytica l competence" is described, the structural components o f analyti cal competence of specialist on economic cybernetics are presented and their content filling is defined,necessity o application of analytical procedures is grounded at the decision of management tasks.
Keywords: дослідження; сутність; процес; аналіз